2017
DOI: 10.3390/cancers9100133
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Integrins in Tumor Metastasis: Do They Represent a Therapeutic Target?

Abstract: Platelets are small anucleated cell fragments that ensure the arrest of bleeding after a vessel wall injury. They are also involved in non-hemostatic function such as development, immunity, inflammation, and in the hematogeneous phase of metastasis. While the role of platelets in tumor metastasis has been recognized for 60 years, the molecular mechanism underlying this process remains largely unclear. Platelets physically and functionally interact with various tumor cells through surface receptors including in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 151 publications
(190 reference statements)
0
50
0
2
Order By: Relevance
“…Although the molecular mechanism is not fully understood, neutrophils seem to interact with platelets and use their adhesive potential, likely via their adhesion receptors, GPIb and αIIbβ3, to attach to the vessel wall, especially under higher shear rates and at atheroslerotic lesions [ 103 ]. Similarly, blood-borne tumor cells during hematogenic dissemination also interact with platelets and subvert their adhesive potential to the vessel wall, likely also mediated via the vWF-receptor and different integrins [ 104 ]. Hence, it is worthwhile to think whether non-hemorrhagic snake venom proteinases which cleave the adhesion receptors on platelets might be useful in reducing platelet-supported extravasation of leukocyte, or disseminating blood-borne tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanism is not fully understood, neutrophils seem to interact with platelets and use their adhesive potential, likely via their adhesion receptors, GPIb and αIIbβ3, to attach to the vessel wall, especially under higher shear rates and at atheroslerotic lesions [ 103 ]. Similarly, blood-borne tumor cells during hematogenic dissemination also interact with platelets and subvert their adhesive potential to the vessel wall, likely also mediated via the vWF-receptor and different integrins [ 104 ]. Hence, it is worthwhile to think whether non-hemorrhagic snake venom proteinases which cleave the adhesion receptors on platelets might be useful in reducing platelet-supported extravasation of leukocyte, or disseminating blood-borne tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet activation and adhesion depend on integrin signaling [ 77 ]. Five integrins, including α2β1, α5β1, α6β1, αIIbβ3 and αvβ3, have been identified in platelets, which bind preferentially to collagen, fibronectin, laminin, vitronectin, and fibrinogen, respectively [ 78 ]. It has been shown that platelet α6β1 mediates the platelet-cancer cell interaction by binding to metalloproteinase (ADAM) 9 on tumor cells, and subsequently induces platelet activation and cancer cell extravasation.…”
Section: Roles Of Platelets In Cancer Development and Progressionmentioning
confidence: 99%
“…Additionally, coating of tumor cells with platelets allows transferring their major histocompatibility complex (MHC) class I to tumor cells, thereby giving these cells a false "pseudonormal" exterior, and allowing escape from immunosurveillence by natural killer cells [149]. TGFβ released by platelets also downregulates the NK receptor NKG2D on tumor cells, further shielding them from immunosurveillence [150,151]. Lastly, extravasation of the tumor cells from the blood stream is facilitated by platelets, and appears to require binding of platelets to Integrin ανβ3 expressed on tumor cells [152].…”
Section: Platelets Drive Tumor Growth Angiogenesis and Metastasis Imentioning
confidence: 99%
“…Tumor-induced angiogenesis often results in an abnormal vasculature with suboptimal perfusion. Nevertheless, tumor cells may benefit from this, as this may reduce delivery of therapies and tumor-targeted immune cells [150]. Furthermore, tumor cells may adapt to such ineffective vascularization, and the ensuing hypoxia may favor tumorigenesis by selecting for aggressive and metastatic clones [153].…”
Section: Platelets Drive Tumor Growth Angiogenesis and Metastasis Imentioning
confidence: 99%